Effects of Green Tea to Absolute Neutrophil Count, MMP-9, %VEP1, and COPD Assessment Test Scores Stable COPD Patients - Hendrastutik Apriningsih; Suradi Suradi; Yusup Subagio Sutanto (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Backgrounds: Chronic obstructive pulmonary disease is the leading cause morbidity and mortality worldwide. Cigarette smoke and noxious agent causing oxidative stress activated nuclear factor-κB then increase inflammatory genes releases. Epigallocatechin-3-gallate green tea have antiiinflammatory effect which can be use as addition therapy for stable COPD. Methods: This study aimed to analyze the effect of EGCG to absolute neutrophil count (ANC), serum MMP-9, %FEV1, and CAT score stable COPD patients. Clinical trials of experimental with pre-test and post-test design was conducted on 30 patients in Dr. Moewardi Hospital Surakarta from February-April 2017. Samples were taken by consecutive sampling divided into treatment group (n=15) received standard therapy and green tea capsule 2x500mg/day during 28 days and control group received only standard therapy (n=15). Decreased inflammation measured by ANC and serum MMP-9, improvement of obstruction measured by %FEV1, and clinic improvement measured by CAT score. Results: There were no significant differences (P=0.135) decrease ANC treatment group (-662.45±1446.80 µL) compared control (413.79±2292.90 µL), decrease serum MMP-9 (P=0.413) treatment group (-324.34±333.56 ng/ml) compared control (-181.21±577.52 ng/ml), %FEV1 (P=0.236) treatment group (2.56±10.77), compared control (-4.30±19.12), and significant difference (P=0.034) CAT score treatment group (-1.07±1.16) compared control (-0.20±1.08). Conclusions: The addition of green tea capsule 2x500 mg/day during 28 days was significantly lowered CAT score, decreasing ANC, serum MMP-9 and increasing %FEV1 but not significant. (J Respir Indo 2018; 38(1): 7-15)